2004
DOI: 10.2337/diabetes.53.3.721
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Pressure-Induced Vasodilation at the Foot in Young Adults With Type 1 Diabetes

Abstract: Vascular and neurological mechanisms are both likely to be involved in foot ulcer. We recently reported a pressure-induced vasodilation (PIV), relying on unmyelinated afferent excitation. We previously found that cutaneous blood flow in response to locally applied pressure might be impaired in diabetic patients because of the combined effects of low cutaneous temperature and alterations in microcirculatory function. Therefore, we aimed to analyze whether, at a relatively high cutaneous temperature, PIV is pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
80
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 94 publications
(88 citation statements)
references
References 44 publications
(38 reference statements)
6
80
2
Order By: Relevance
“…These results are in accordance with those obtained in diabetic patients (40). These findings point out that PIV response seems to be highly sensitive to endothelial NO levels, and therefore endothelial impairment by itself is sufficient to alter severely the PIV response.…”
Section: Discussionsupporting
confidence: 82%
“…These results are in accordance with those obtained in diabetic patients (40). These findings point out that PIV response seems to be highly sensitive to endothelial NO levels, and therefore endothelial impairment by itself is sufficient to alter severely the PIV response.…”
Section: Discussionsupporting
confidence: 82%
“…Previous studies of PIV have used LDF, and by using the same measurement technique the results are easier to compare (Abraham et al, 2001;B. Fromy et al, 2010;Koïtka et al, 2004). The baseline threshold was chosen based on a previous study by Sanada et al (1997) who showed that patients who had an inability to increase blood flow over baseline values during long pressure exposures were the ones who tended to develop pressure ulcers.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of PIV leads to a decrease in blood flow even in response to low levels of pressure, and this makes the individual vulnerable to externally applied pressure. The PIV function has been shown to be altered in diabetic patients (Koïtka et al, 2004) and in the elderly Fromy et al, 2010), but a lack of PIV response can also be found in young, healthy individuals . With progressively increasing pressure to the skin, the PIV response has been shown to reach its maximum at pressure levels of 25-50 mmHg in young, healthy individuals (Fromy et al, 2010;Schubert & Fagrell, 1989).…”
Section: Blood Flow Responses Related To Loadingmentioning
confidence: 99%
“…Impaired vasodilatory response to plantar pressure causing tissue ischemia is the common final pathway, according to various theories, of the development of diabetic foot ulcers (Boulton et al, 2000). Diabetic patients (with or without peripheral neuropathy) suffer from various forms of microvascular dysfunction, including abnormal vasomotion (Benbow et al, 1995;Stansberry et al, 1996;Bernardi et al, 1997), impaired vasodilatory response to local heating (Malik et al, 1993;Stansberry et al, 1999), decreased blood flow under or after pressure loading (Fromy et al, 2002;Koitka et al, 2004), endothelial nitric oxide dysfunction (Veves et al, 1998), and attenuated response to sympathetic maneuvers (Aso et al, 1997).…”
Section: Microvascular Factors and Ulcerationmentioning
confidence: 99%